Drivers and drawbacks of environmental innovation – empirical analysis of the Hungarian chemical sector - Szűcs, Gergely (REGIONAL AND BUSINESS STUDIES, 2011)
The empirical study is based on 70 structured interviews with representatives of Hungarian chemical companies carried out by the Budapest Corvinus University in April-May 2010. The 70 companies reported 104 environmental innovations in the last three years. In the cases of 102 innovations, they reported also the degree of innovativeness. Smaller companies (especially microcompanies) have fewer financial resources to realise environmental innovations. Yet this is only true on a 61-72% significance level in cases where small companies had access to external financial sources. About three-quarters of all environmental innovations are adaptations of existing technology. Novel innovations, although fewer in number, seem to have a bigger influence on environmental improvement than adaptations. Considering that these novel innovations can then be adapted by other companies, they have outstanding significance. I analysed the relationship between the novelty of innovations and the financial position of the company producing them. I found that there is a difference between the return on investment in novel innovations and adaptations favouring the former. Companies in the worst financial position find it hard to accomplish novel innovations, very few of them pursue these instead of adaptations. Companies with average or above average financial position (64-70% in our sample) are able to achieve novel innovations.Keywords: Environment, innovation, chemistry